DESKRIPSI KECERDASAN EMOSIONAL MATEMATIS PESERTA DIDIK KELAS XI DALAM PEMBELAJARAN MATEMATIKA - Andita Pramizha; Indrie Noor Aini (Universitas Muhammadiyah Metro, 2023)
This study aims to determine the level of mathematical emotional quotient of Class XI students at SMKN 1 Rawamerta in the 2022/2023 academic year. The type of research applied is descriptive qualitative using survey methods. Simple random sampling was used to select the sample, resulting 32 students in Class XI TKRO 3. The data were obtained from a mathematical emotional quotient questionnaire containing 25 statements using a Likert scale rating. The research was conducted so that researchers can find out the answers of students who show their emotional quotient in the process of learning mathematics. Based on the results and discussion, it shows that the percentage of all students is 71%. So, the level of emotional intelligence of Class XI students at SMKN 1 Rawamerta is in the sufficient category.